Exercise physiology for health, fitness, and performance - Plowman, Sharon A.; Smith, Denise L. (Philadelphia Wolters Kluwer, 2017)
The new edition of Plowman and Smith's renowned text continues to the authoritative textbook for teaching Exercise Physiology. This engaging and beautifully designed text integrates theoretical and research based basic exercise physiology with real-world application to prepare students for exciting positions in exercise science, fitness, physical education, athletic training, rehabilitation, coaching and/or allied health professions. Accessible and engaging, the 5th Edition offers coverage of foundational science and critical exercise physiology topics. Organized by independent units (Metabolic, Cardiovascular-respiratory, Neuromuscular-skeletal, and Neuroendocrine-immune) this text offers maximum teaching flexibility for faculty and consistent presentation of material for the student.
The warm-up -- Energy production -- Anaerobic metabolism during exercise -- Aerobic metabolism during exercise -- Metabolic training principles and adaptations -- Nutrition for fitness and athletics -- Body composition : determination and importance -- Body composition and weight control -- Respiration -- Respiratory exercise response, training adaptations, and special considerations -- The cardiovascular system -- Cardiovascular responses to exercise -- Cardiorespiratory training principles and adaptations -- Thermoregulation -- Cardiovascular disease risk factors and physical activity -- Skeletal system -- Skeletal muscle system -- Muscular contraction and movement -- Muscular training principles and adaptations -- Neuromuscular aspects of movement -- Neuroendocrine control of exercise -- The immune system, exercise, training, and illness.
Includes bibliographical references and index.
Keywords: Exercise -- Physiological aspects; Sports Nutritional Physiological Phenomena